Economic organization - "Ghadoliya , M. K." (New Delhi, 1987)
The paper on the subject of Economic Organisation for Undergraduate classes of some of the Universities in India has been designed in such a way that students gain preliminary understanding of the functioning of the various aspects of the Indian Economy. It cover up many topics pertaining to different fields of Economic Analysis, such as Economic Problems, Resource Alocation, Factors of Production, National Income, Development Money, Banking, Forms of Business organisation and Economic Systems. It is true that no University student would find all his text in one volume. But in present volume an attempt has been made to cover the most of the topics to serve the needs of the students.
Keywords: Business enterprises